Evolutionary significance of the retiolitine Gothograptus (Graptolithina) with four new species from the Silurian of the East European Platform (Baltica), Poland and Lithuania - Kozłowska, Anna; Bates, Denis; Zalasiewicz, Jan; Radzevičius, Sigitas (Zootaxa, 2019)
Gothograptid retiolitines were distinctive in being one of the very few graptolite groups to thrive through the late Wenlock extinction event that killed off most graptoloid species, and their distinctive construction may have been a factor in this success amid environmental adversity. New and rich material from two localities in Poland and five localities in Lithuania contains Gothograptus nassa, Gothograptus obtectus and four new species. The detailed morphology and reconstruction of the tubarium shows its specific features, different from other lundgreni Biozone retiolitines. The tubarium is narrow, elongated, finite, massive and compact. The thecal orifices are hidden by simple hoods or by extraordinary reticulated veils, which may cover the ventral walls. The colonies of Gothograptus species from the lundgreni Biozone are short, usually having eight pairs of thecae, whereas species from the post-lundgreni interval may reach more than 20 pairs of thecae. A common feature of Gothograptus species is the presence of singular genicular structures tightly covering thecal orifices. Reticulated hoods and veils are characteristic of species from the lundgreni Biozone. The most common such structures are nassa hoods, located on the proximal thecae in some species from the lundgreni Biozone, and on every theca of post-lundgreni species. Only Gothograptus domeyki n. sp. has no genicular processes on most thecae. Within a total of four species from the lundgreni Biozone and three species from the nassa and praedeubeli Biozones, we describe here the new species Gothograptus domeyki and Gothograptus velo from the lundgreni Biozone, Gothograptus diminutus from the parvus/nassa Biozone, and Gothograptus auriculatus from the dubius/nassa and praedeubeli biozones; G. auriculatus n. sp. is the youngest form of the genus Gothograptus. Variation within the genus Gothograptus during the post-lundgreni interval period is shown for the first time.